Characterization of Isogrid Structure in GFRP (Fracture and Structural Integrity, 2018)
Lightening parts, maintaining also a high strength, is a request of the transport industry. Isogrid structures represent one of the best answer to face these issues, especially if composite materials are considered for their production. However, the fabrication of these structures is very complex, as defects can arise that cause the part discarding or the part failure during service. The properties of the fabricated structure depend on some process characteristics, as the forming technology, the process parameters and the tools that have to be wisely designed. Isogrid structures are characterized by the ribs, so the mould shape must be carefully planned. In fact, a common defect that usually occurs is a scarce compaction of the ribs, which involves porosity and low mechanical strength.In this paper, the manufacturing process peculiarities for GFRP (Glass Fibre Reinforced Polymer) isogrid structures were defined, then both the mould and the parts were produced. Structural tests were carried out on these structures in order to validate the process design methodology, paying particular attention to the structural properties of the ribs, as the compaction degree and the interlaminar shear strength. Finally, some actions were undertaken to avoid the problems found in the first production run.
Keywords: Isogrid structures; Composite materials; Curing; Interlaminar shear strength; Complex shape